Transforming the Northeast Tackling Backlogs In Basic Minimum Services and Infrastructural Needs High Level Commission Report To the Prime Minister Executive Summary - Planning Commission (Planning Commission, 1997)
This report, commissioned by the Planning Commission under the Prime Minister’s New Initiatives for the North Eastern Region, assesses the backlog in Basic Minimum Services (BMS) and infrastructure across Northeast India. It identifies significant deficits in housing, education, health, power, roads, and railways, with a total estimated funding requirement of over Rs. 1,03,000 crores. The report highlights challenges such as political neglect, socio-economic isolation, insurgency, and geographic constraints. Recommendations focus on recruiting qualified personnel, improving transparency, promoting agricultural development, enhancing infrastructure through public-private partnerships, conserving biodiversity, boosting tourism, and fostering inter-state trade. A robust monitoring and evaluation framework is proposed to ensure effective implementation. The study concludes that comprehensive and coordinated efforts by central and state governments are essential to transform the Northeast into a region of strategic and economic significance.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Northeast India; Basic Minimum Services; Infrastructure Development; Economic Package; Agricultural Development; Power Sector; Roads and Railways; Tourism Promotion; Public-Private Partnerships; Monitoring and Evaluation